Data security and public trust in the digitalization of health insurance in Indonesia: A literature review - Amanda Safitri; Nadia Putri Untiami; Siti Aisyah; Cahya Arbitera (Indonesian Journal of Health Science, 2026)
The digitalization of health insurance in Indonesia, particularly in the implementation of the National Health Insurance (JKN) program, offers significant benefits in improving the efficiency and accessibility of healthcare services. However, this digital transformation also presents serious challenges related to data security and public trust. This study aims to examine the relationship between data security and public trust in the context of health insurance digitalization through a literature review approach. The method used is descriptive-analytical by reviewing relevant scientific articles published between 2020 and 2026, obtained from databases such as Google Scholar, Garuda, and other international sources. The findings indicate that data security risks, including data breaches, cybercrime, and weak data governance, are key factors that may reduce public trust in digital health insurance services. In addition, non-technical factors such as low privacy literacy and human error further increase system vulnerabilities. On the other hand, public trust is influenced not only by technical security but also by perceived benefits, transparency, and ethical governance. Therefore, strengthening data security systems, adopting innovative technologies, and developing trust-based governance are essential to support the sustainability of health insurance digitalization in Indonesia.